Failure of the Pipeline Embolization Device in Posterior Communicating Artery Aneurysms Associated with a Fetal Posterior Cerebral Artery - Mario Zanaty; Nohra Chalouhi; Robert M. Starke; Pascal Jabbour; Katherine O. Ryken; Ketan R. Bulsara; David Hasan (Case Reports in Vascular Medicine)
The pipeline embolization device has emerged as an important endovascular option. This is in part due to safety, efficacy, and possibly the ability to shorten the operative time considerably. With this new technology, some limitations are emerging as experience accumulates. We report three cases of posterior communicating (PCOM) artery aneurysms associated with fetal posterior cerebral artery where pipeline embolization was unsuccessful in obliterating the aneurysms. PCOM artery aneurysms associated with a fetal PCA should be managed either by microsurgical clipping or coiling when feasible.